Studi Pembuatan Biskuit Fungsional dengan Substitusi Tepung Ikan Gabus dan Tepung Daun Kelor - Rina Sugiarti Dwi Gita; Sarwo Danuji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aims of this study are to develop a Science Process Skills Based Module (KPS) on Cell-Level Life Organization Materials for Grade VII Students of SMP Kristen 2 Salatiga. This research is a research development (R & D) with an F-D development model (Define, Design, Develop, and Disseminate), but in this study it does not cover the entire stages in the F-D development model, namely the disseminate stage because of the limitations of the time the research was conducted. The instruments in this study were interview sheets, validation sheets, and student response sheets. The results of module development research according to the expert validity test 3.1, test pedagogical validity 3.15, test the validity of practitioner experts 3.08, and limited field testing 3.37, from the overall data obtained shows that the average module values ​​above 3.00 and is categorized as